The Use of Direct Reading Thinking Activity (DRTA) to Improve Students’ Narrative Text Reading Comprehension - Moh. Fadil; Muhammad Ihsan; Dzakiah, Dzakiah (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2024)
This study examines the effectiveness of the Direct Reading Thinking Activity (DRTA) technique in improving the ability of ninth-grade students at MTs Alkhairaat Alindau to understand and comprehend narrative texts. The main study inquiry investigates the efficacy of the DRTA technique in enhancing students' reading comprehension abilities. The research utilizes a quantitative methodology and follows a pre-experimental design, specifically employing a one-group pretest-posttest framework. The study included a total of 27 ninth-grade students, who serve as both the population and sample. The data gathering process involved administering pretests and posttests, while the analysis utilized descriptive statistics, T-tests, and hypothesis testing. The results suggest that the DRTA technique has a substantial positive impact on pupils' reading comprehension. The initial average score was 46.29, and the statistical analysis showed that the calculated t-value (6.998) was higher than the critical t-value (1.708), resulting in the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). These findings demonstrate that implementing the Directed Reading-Thinking Activity (DRTA) technique effectively enhances the narrative text reading comprehension of ninth-grade students at MTs Alkhairaat Alindau.